The book club - Cooper, C. J. (Constable, 2020)
"The book club was her idea, of course. It was her way into our group. A chance to get close. I knew from the day she arrived that she couldn't be trusted. And I was right. Because Alice didn't come to the village for peace and quiet. She came for revenge." Having said goodbye to her old life in London, and the disastrous affair that sent her packing, twenty-something Lucy Shaw decides to move to the picture-perfect Cotswolds village of Willowcombe. When newcomer Alice Darley moves into the cottage next door mere months after her own arrival, Lucy's new friends are very welcoming, especially when Alice suggests setting up a book club. But there's something about Alice that doesn't sit well with Lucy - and as the group begin to see eerie parallels between the stories being discussed and the hidden truths of their own lives, they each begin to fear that the book club will expose their deepest, darkest secrets. And with neighbour turning against neighbour, Lucy is about to discover that Alice's twisted games are only just beginning . . ."--Provided by publisher.